BRCA1 haploinsufficiency impairs iron metabolism to promote chrysotile‐induced mesothelioma via ferroptosis resistance. Issue 4 (2nd February 2023) - Luo, Yaguang; Akatsuka, Shinya; Motooka, Yashiro; Kong, Yingyi; Zheng, Hao; Mashimo, Tomoji; Imaoka, Tatsuhiko; Toyokuni, Shinya
Abstract: Malignant mesothelioma (MM) is still a social burden associated with asbestos exposure. Local iron accumulation thereby represents the major pathogenesis, followed by oxidative DNA strand breaks and genomic alterations in the mesothelium. BRCA1 is a critical component of homologous recombination repair directed to DNA double‐stranded breaks, whereas BRCA1 germline mutation is an established risk for breast/ovarian cancer, its role in MM development remains to be elucidated. Murine Brca1 mutant models so far have not reproduced human phenotypes. However, a rat Brca1 mutant model (Mut; L63X/+ ) recently reproduced them at least partially. Here we describe the differential induction of MM in Brca1 mutant rats by intraperitoneal injection of chrysotile or crocidolite. Only Mut males injected with chrysotile revealed a promotional effect on mesothelial carcinogenesis in comparison with wild‐type and/or females, with all the MMs Brca1 haploinsufficient. Array‐based comparative genomic hybridization of MMs disclosed a greater extent of chromosomal deletions in Brca1 mutants, including Cdkn2a / 2b accompanied by Tfr2 amplification, in comparison with wild‐type tumors. Mutant MMs indicated iron metabolism dysregulation, such as an increase in catalytic Fe(II) and Ki67‐index as well as a decrease in Fe(III) and ferritin expression. Simultaneously, mutant MMs revealed ferroptosis resistance by upregulation of Slc7A11 and Gpx4. At an early carcinogenic stage of 4 weeks, induced Brca1 expression in mesothelial cells was significantly suppressed in chrysotile/Mut in comparison with crocidolite/Mut, whereas significant preference to iron with a decrease in Fe(III) has been already established. In conclusion, chrysotile exposure can be a higher risk for MM in BRCA1 mutant males, considering the rat results. Abstract : We describe the differential induction of malignant mesothelioma in Brca1 mutant rats (Mut; L63X/+) by intraperitoneal injection either of chrysotile or crocidolite. Chrysotile exposure can be a higher risk for MM in BRCA1 mutant males.